2000
DOI: 10.1074/jbc.m003902200
|View full text |Cite
|
Sign up to set email alerts
|

The IκB Kinase (IKK) Complex Is Tripartite and Contains IKKγ but Not IKAP as a Regular Component

Abstract: A critical step in the activation of NF-B is the phosphorylation of IBs by the IB kinase (IKK) complex. IKK␣ and IKK␤ are the two catalytic subunits of the IKK complex and two additional molecules, IKK␥/NEMO and IKAP, have been described as further integral members. We have analyzed the function of both proteins for IKK complex composition and NF-B signaling. IKAP and IKK␥ belong to distinct cellular complexes. Quantitative association of IKK␥ was observed with IKK␣ and IKK␤. In contrast IKAP was complexed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
88
1
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(95 citation statements)
references
References 41 publications
5
88
1
1
Order By: Relevance
“…2F). These observations are supported by an earlier study in which IKAP was also shown to localize mainly in the cytosol using cell fractionation and Western blot analysis, utilizing a different IKAP antibody from what we use in this study (2). We conclude that the vast majority of IKAP is cytoplasmic.…”
Section: Cloning Of Ikap; Jnk Associates With Ikap In Vivo Andsupporting
confidence: 79%
See 1 more Smart Citation
“…2F). These observations are supported by an earlier study in which IKAP was also shown to localize mainly in the cytosol using cell fractionation and Western blot analysis, utilizing a different IKAP antibody from what we use in this study (2). We conclude that the vast majority of IKAP is cytoplasmic.…”
Section: Cloning Of Ikap; Jnk Associates With Ikap In Vivo Andsupporting
confidence: 79%
“…A later report by Krappmann et al (2) cast doubt on the role of IKAP in the NF-B pathway. Using a gel filtration approach, these authors were unable to detect IKAP in the fractions containing IKK complexes.…”
Section: Ikapmentioning
confidence: 99%
“…This may lead to increased IKK␤ phosphorylation of IB␣ and IB␤ and thus result in enhanced IB degradation and NF-B nuclear translocation. Previous studies indicate that IKK␣, IKK␤, and IKK␥/ NEMO interact in the high molecular weight IKK complex (35,36,40). Our previous studies indicate that the high molecular weight IKK complex can be formed in COS cell extracts prepared following transfection of expression vectors encoding epitope-tagged IKK␣, IKK␤, and IKK␥/NEMO (41).…”
Section: Ikk␥/nemo Stimulates Ikk␤ Phosphorylation Of Ib␣ Andmentioning
confidence: 99%
“…IKK␥/NEMO in conjunction with IKK␣ and IKK␤ is a component of the high molecular weight IKK complex, which migrates between 600 and 900 kDa following gel filtration chromatography (12, 14, 29, 34 -41). Biochemical fractionation and coimmunoprecipitation studies demonstrate that IKK␣, IKK␤, and IKK␥/NEMO interact in this IKK complex (35,36,40). Cells that do not express IKK␥/ NEMO are unable to assemble the high molecular weight IKK complex and increase IKK activity in response to agents that stimulate the NF-B pathway (35,36).…”
mentioning
confidence: 99%
See 1 more Smart Citation